Theoretical perspectives of psychosocial intervention: applications in boys, girls and adolescents in the street situation - Caicedo Córdoba , Jessy Julissa; Perozo Álvarez , Diana Beatriz (Interacción y Perspectiva, 2024)
The objective of this essay is to analyze the relationship between Erickson’s Psychosocial Theory, Bronfenbrenner’s Ecological Theory and the work of the social worker, when designing and developing a social intervention to attend to cases of children and adolescents in street situations. The methodology is documentary, following Hernández S, et al. (2021), using primary and original documentary sources, considering the results of the authors’ research; as well as secondary documentary sources, printed and electronic. The analysis process involved developing a motivating thesis, discovering the antithesis of the approach and offering a synthesis: This is systematized here, providing some criteria to develop the necessary foundation, which provides a conceptual and theoretical basis focused on psychosocial aspects, to understand and address the phenomenon of street children and adolescents, including basic definitions, their representatives, theories and methods. After this synthesis, it closes with some final reflections, fulfilling the objective of the essay, having analyzed the relationship between the aforementioned theories and the professional work of the social worker, when designing and developing a social intervention to attend to cases of children and adolescents in street situations.